Application of the Rasch Model for Validating Representational Systems and Chemical Reactions Diagnostic Instrument (RSCRDI) - Lestari, Yusfa; Hasanuddin, Nurqadriyanti; Ira Saputri, Sukmawati; Zulfi Maulidita, Salizmi (Saqbe: Jurnal Sains dan Pembelajarannya, 2024)
This study seeks to evaluate the validity and reliability of the outcomes derived from the adoption of the Representational Systems and Chemical Reactions Diagnostic Instrument (RSCRDI). This research employs a quantitative, survey-based approach, involving 69 prospective chemistry teachers at a university in Indonesia. Prior to implementation, the instrument was translated from English to Indonesian using the back-translation method. The collected data were subsequently analyzed using Winstep, yielding strong validity and reliability results. The instrument exhibited a Cronbach's alpha of 0.65, a person reliability of 0.60, and an item reliability of 0.76. Furthermore, the construct validation results were favorable, as evidenced by mean score (MNSQ), Z-standard (ZSTD), and point measure correlation (Pt Mea Corr) indices. These findings indicate that the RSCRDI is a valid and reliable instrument for assessing conceptual understanding among prospective chemistry teachers in Indonesia.